Desenvolvimento de um modelo de indicadores de gestão de pessoas: o caso dos institutos federais de educação, ciência e tecnologia - Bassi, Eduardo da Rocha (2015)
According to Bergue (2014) and the MPOG (2009), measuring outputs in public administration is one of the main tools to support managers in decision making, to establish parameters (ASSIS, 2012) and to compare results (POMI, 2002). However, even being aware of the importance and the need to develop, use and publicize these indicators, many of the Federal Institutes of Education, Science and Technology (IFETs) still lack indicators for personnel management. In this sense, the present case study aimed to develop a model of Human Resource Management Indicators for the Federal Institutes in order to contribute to management decision-making and to facilitate the transparency of information to society and to the regulatory agencies. This work is a descriptive and prescribed research of qualitative nature. Regarding the technical procedures, it was applied both bibliographical, documental and field research. The data was collected in 228 management reports, obtained from the TCU database, and from interviews with managers of three IFETs, and it was analyzed using content analysis. Initial results showed that currently only 15 (fifteen) of the 38 (thirty-eight) Federal Institutes have a model of Human Resource Management Indicators containing one or more indicators, and that the main difficulties encountered by IFETs in applying these indicators are related to: shortage of staff; lack of an information system; prioritization of other activities; lack of interest by management; and the absence of a standardized model of indicators. Subsequently, based on the results of the bibliographical and documental analysis, a model composed of 9 (nine) Human Resource Management Indicators was formatted, those being collected and considered in order of preference (practical application) and theoretical support: Absenteeism; Rate of accidents and occupational diseases; Remoteness rate; Retirement forecast; Retirement replacement; Capacity building; Variation in the number of staff; Qualification level; Turnover. This model was evaluated by personnel managers of three Federal Institutes (IF Farroupilha, IFRS and IF Sul) and, in general, the proposed indicators met the essential requirements recommended by MPOG (2010) and other authors. In addition, the respondents consider that almost all indicators presented have practical application, and that the model may contribute to management decision-making and can facilitate transparency of information to society and to the regulatory agencies.